Gene network analysis of oxaliplatin-resistant colorectal cancer to target a crucial gene using chitosan/hyaluronic acid/protamine polyplexes containing CRISPR-Cas9 - Shirani-Bidabadi, Shiva; Mirian, Mina; Varshosaz, Jaleh; Tavazohi, Nazita; Sadeghi, Hamid Mir Mohammad; Shariati, Laleh (Biochimica et biophysica acta. General subjects, 2023)
Colorectal cancer (CRC) treatment is dramatically hampered by resistance to oxaliplatin alone or in the combination of irinotecan or 5-fluorouracil and leucovorin. This study aims to design and assess Chitosan/Hyaluronic Acid/Protamine sulfate (CS/HA/PS) polyplexes loaded with CRISPR plasmid for targeting a key gene in cancer drug resistance. Here, recent findings were considered to validate oxaliplatin-resistant CRC-related genes and systems biology approaches employed to detect the critical gene. The polyplexes were characterized according to particle size, zeta potential, and stability. Moreover, carrier toxicity and transfection efficiency were assessed on oxaliplatin-resistant HT-29 cells. The post-transfection evaluations were performed to confirm gene disruption-mediated CRISPR. Eventually, excision cross complementation group 1(ERCC1), a crucial member of the nucleotide excision repair pathway, was selected to be targeted using CRISPR/Cas9 to reverse oxaliplatin resistance in HT-29 cells. CS/HA/PS polyplexes containing CRISPR/Cas9 plasmid exhibited negligible toxicity and comparable transfection efficiency with Lipofectamine™. Following the efficient gene delivery, sequences in CRISPR/Cas9 target sites were altered, ERCC1 was downregulated, and drug sensitivity was successfully restored in oxaliplatin-resistant cells. Findings indicate that CS/HA/PS/CRISPR polyplexes provide a potential strategy for delivering cargo and targeting oxaliplatin resistance-related gene to manipulate drug resistance as a rising concern in cancer therapeutic approaches. [Display omitted] •Gene-network analysis highlight ERCC1 as a critical gene in oxaliplatin resistance.•Chitosan/hyaluronic acid/protamine polyplexes loaded CRISPR enhance transfection.•Inducing ERCC1 mutations restored oxaliplatin sensitivity.